Optimization of inventory distribution in clinical trial supply chain - Chan, Jason Wei Long (2014)
In the pharmaceutical industry, the development process that required bringing a new drug to market involves significant expenses and long period of time. Clinical trial constitutes an important part in the development process. The main issue in managing clinical trials is patient recruitment. As the demand is uncertainty in the clinical trial, it is important to maintain enough inventories when the patient arrives for treatment. This research aims to investigate the inventory decision made within clinical trial supply chain, which involves demand forecasting based on patient enrolment process. The objective of this project is to allocate limited amount of inventory to satisfy the stochastic demand and to minimize the inventory costs which include delivery and underage cost for all scenarios. A two-stage stochastic linear programming model with rolling was proposed. In the model, a distribution network consists of one distribution centre and three clinical sites are used in this research. The optimization model is run by using IBM CPLEX Optimizer to determine and achieve a satisfactory level of customer demand while keeping the inventory level at the clinical sites and the inventory cost reasonable.